Design of Temperature Instrument of WIA-PA Wireless Industrial Network - YAN A-ren; LIU Feng (Gong-kuang zidonghua, 2011)
The paper proposed a design scheme of temperature instrument of WIA-PA wireless industrial network, analyzed technical features of WIA-PA and detailedly introduced design of hardware and software of the temperature instrument. The actual application showed that the temperature instrument runs stably and meets with working requirements of WIA-PA for field devices of wireless industrial network.